Method of justification of organizational and technical measures for improvement of ship equipment operation - Крынцыло, Вадим Анатольевич (Eastern-European Journal of Enterprise Technologies, 2013)
The method of justification of practical recommendations on the improvement of operating processes of ship technical means (hereinafter − STM) by estimating the efficiency and safety of the specified processes is proposed in the paper. The essence of the method lies in the formalized representation of the STM operating process as the graph of work, source data formation in the structure of probabilistic and resource characteristics for each operation of the process under investigation with further phased recalculation of these characteristics during the integration of the graph of work. As a result, the technical condition of STM is defined, effectiveness and safety indexes of the whole operating process are calculated, the analysis results of which allow the decision-making on the further improvement of the process under investigation. Unlike the existing methods, the developed method allows taking into account many technical states of STM and types of personnel errors, as well as assessing not only the correctness and timeliness of taking the operational measures, but also the safety of the operating processes of STM